2012
DOI: 10.1371/journal.pgen.1003099
|View full text |Cite
|
Sign up to set email alerts
|

A Yeast GSK-3 Kinase Mck1 Promotes Cdc6 Degradation to Inhibit DNA Re-Replication

Abstract: Cdc6p is an essential component of the pre-replicative complex (pre-RC), which binds to DNA replication origins to promote initiation of DNA replication. Only once per cell cycle does DNA replication take place. After initiation, the pre-RC components are disassembled in order to prevent re-replication. It has been shown that the N-terminal region of Cdc6p is targeted for degradation after phosphorylation by Cyclin Dependent Kinase (CDK). Here we show that Mck1p, a yeast homologue of GSK-3 kinase, is also requ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
45
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(47 citation statements)
references
References 53 publications
(79 reference statements)
2
45
0
Order By: Relevance
“…Thus, Cdc6 is selectively degraded in a Mck1-dependent manner after membrane damage. Previously, we showed that Mck1 phosphorylates Cdc6 at T39 and T368 (30,31). Motivated by these findings, we tested if the Cdc6 phosphorylation mutant, Cdc6-T39A-T368A, is stabilized upon SDS stress.…”
Section: Plasma Membrane Damage Inhibits Dna Replication Through Cdc6mentioning
confidence: 97%
See 2 more Smart Citations
“…Thus, Cdc6 is selectively degraded in a Mck1-dependent manner after membrane damage. Previously, we showed that Mck1 phosphorylates Cdc6 at T39 and T368 (30,31). Motivated by these findings, we tested if the Cdc6 phosphorylation mutant, Cdc6-T39A-T368A, is stabilized upon SDS stress.…”
Section: Plasma Membrane Damage Inhibits Dna Replication Through Cdc6mentioning
confidence: 97%
“…S3B). Previously, we showed that Cdc6 degradation is mediated by Mck1 during an unperturbed cell cycle or during a DNA damage response (30,31). Δmck1 deletion cells are sensitive to various stress stimuli, including plasma membrane stress (Fig.…”
Section: Plasma Membrane Damage Inhibits Dna Replication Through Cdc6mentioning
confidence: 99%
See 1 more Smart Citation
“…Mck1 phosphorylates its substrates at a consensus site that contains a priming phosphorylated residue in the +4 position (26). Subsequent phosphorylation by Mck1 generates a di-phosphorylation matching the Cdc4 phospho-degron spacing, and Mck1 has been implicated previously in controlling turnover of several Cdc4 substrates (23,(27)(28)(29). Two of the phosphorylation sites we identified by mass spectrometry, T380 and S416, exactly match the Mck1 consensus (with a phosphorylated residue in the +4 position).…”
Section: Significancementioning
confidence: 57%
“…6A) strongly suggest that residues other than Hst3 Thr-380/ Thr-384 can be phosphorylated by CDKs. It is also possible that phosphorylation of non-CDK sites may contribute to Hst3 deg- radation, as has been observed for some substrates of SCF Cdc4 and SCF Fbw7 (29,49,51). Hst4 is redundant with Hst3 for H3K56 deacetylation, and interestingly, Hst4 was previously identified through a screen for proteins that directly bind to Cdc4 (25).…”
Section: Discussionmentioning
confidence: 90%